Implementation of Employee Motivation in the Gowa Regency Office's General Area - Asir, Muhammad; Rachman, Siswati (Budapest International Research and Critics University, 2021)
Motivation is the process of encouraging someone to work harder in order to accomplish a goal. Motivation is critical in an institution if it is to enhance labor production. The aim of this study is to investigate how to motivate staff in the general area of the Gowa Regency Office'S General Area. The author employs a descriptive qualitative approach, in which she explains the findings of observations and direct interviews with those who supply inspiration to employees and employees who get motivation from leaders/superiors. This study was conducted from June to August 2021. The study's findings indicated that the General Section of the Gowa Regent's Office motivated employees through effective communication, involving employees in delivering ideas/opinions, providing remuneration commensurate with responsibility, presents/incentives, security, and work safety. The motivation to view employees' conduct and needs in terms of their degree or rank.